Adquisitorial: the mixing of two legal systems - Quadri, Kafayat Motilewa; Kadouf, Hunud Abia; Eishan Jan, Mohammad Naqib; Abdul Wahab, Mohd Iqbal; Ahamat, Haniff (International Scientific Academy of Engineering & Technology (ISAET), 2015)
Adquisitorial is a concept that embodies the actuality of a fusion of two legal systems in order to achieve sustainable justice through the merging of best practices from the adversarial and inquisitorial methods of criminal procedure. There are some national courts and even international bodies such as the ICC that have started operating the adquisitorial method. Ample examples can be found in the South African Laws and in the Rome Statute of the International Criminal Court. It had been noted that the procedure used by ICC shows the characteristics of the Common Law System or Adversarial System and the Civil Law System or Inquisitorial System in a mixed mode. This paper will look into the play out of criminal trials using the adversarial method on one hand and the inquisitorial method on the other hand; and then finally look into systems that are practicing the mixed system of adquisitorial. .